Nutritional and Biochemical Analysis of Locally Produced Wine from a Blend of Banana (Musa sapientum) and Date Palm Fruit (Phoenix dactylifera L.) - Tatah, Silas Verwiyeh; Shadrach, Philip; Abah, Moses Adondua (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Background: Wine is a low-alcohol beverage made from fresh grapes or grape juice through partial or complete fermentation. Wine contains many nutrients necessary for the human body, such as sugar, vitamins, amino acids, mineral elements, polyphenols etc. Objective: This project aimed at analysing the nutritional and biochemical composition of locally produced wine from a blend of banana and dates palm fruit. The study includes determining the proximate, phytochemical, mineral, physicochemical, and amino acid profiles. Methods: The method involves heating a crucible dish to eliminate moisture, determining fat content, defatting the sample, determining ash, and determining crude protein. The phytochemical analysis includes tests for saponin, flavonoid, alkaloid, and tannin. Mineral analysis was carried using an atomic absorption spectrophotometer, while physicochemical analysis includes alcohol, pH, and temperature measurements as well as determination of amino acid profile analysis of banana-date palm wine. Results: The proximate analysis revealed high moisture content (97.87%), suggesting a good source of fruit wine production. The wine contains low crude fibre (1.01%), low crude protein (0.14%), Ash content (0.49%) and low crude lipid (0.58%). The wine also contains antioxidant and anti-inflammatory properties. Physicochemical analysis revealed an average pH of 4.62 to 4.71, with sugar concentration decreasing daily over four days and two mineral elements were reveal which are potassium and phosphorus. The amino acid profile analysis of banana-date palm wine reveals that it contains both essential and non-essential amino acids. The essential amino acids include isoleucine, methionine, histidine, and phenylalanine, non-essential amino acids include glutamic acid, asparagine, proline, and cysteine. Conclusion: The findings of this study suggest that a blend of Banana (musa sapientum) and date palm fruit (Phoenix dactyliferal) wine has a unique pleasant aroma, and may have the potential to provide both essential and non-essential amino acids, provide other nutrients that are important for normal physiological function of the body.